Network scanning cookbook practical network security using Nmap and Nessus 7 - Sairam, Jetty (Packt Publishing, 2018)
Discover network vulnerabilities and threats to design effective network security strategies Key Features Plunge into scanning techniques using the most popular tools Effective vulnerability assessment techniques to safeguard network infrastructure Explore the Nmap Scripting Engine (NSE) and the features used for port and vulnerability scanning Book Description Network scanning is a discipline of network security that identifies active hosts on networks and determining whether there are any vulnerabilities that could be exploited. Nessus and Nmap are among the top tools that enable you to scan your network for vulnerabilities and open ports, which can be used as back doors into a network. Network Scanning Cookbook contains recipes for configuring these tools in your infrastructure that get you started with scanning ports, services, and devices in your network. As you progress through the chapters, you will learn how to carry out various key scanning tasks, such as firewall detection, OS detection, and access management, and will look at problems related to vulnerability scanning and exploitation in the network. The book also contains recipes for assessing remote services and the security risks that they bring to a network infrastructure. By the end of the book, you will be familiar with industry-grade tools for network scanning, and techniques for vulnerability scanning and network protection. What you will learn Install and configure Nmap and Nessus in your network infrastructure Perform host discovery to identify network devices Explore best practices for vulnerability scanning and risk assessment Understand network enumeration with Nessus and Nmap Carry out configuration audit using Nessus for various platforms Write custom Nessus and Nmap scripts on your own Who this book is for If you're a network engineer or information security professional wanting to protect your networks and perform advanced scanning and remediation for your network infrastructure, this book is for you